Trends in Private Equity Acquisition of Orthopaedic Surgery Practices in the United States. (December 2021) - Mikhail, Christopher; Shankar, Dhruv; Taree, Amir; Mody, Kush; Barbera, Joseph; Okewunmi, Jeffrey; Cho, Samuel; Anthony, Shawn
Abstract : Background: Independent orthopaedic practices in the United States have become attractive targets for acquisition by hospital systems and private equity (PE) firms because of the increasing demand for outpatient surgery. Consolidation in this market will have notable effects on the delivery and cost of orthopaedic services. In this study, we identified major trends in orthopaedic practice acquisitions over the past decade. Methods: A list of acquisition deals between 2010 and 2019 was compiled from four business databases: S&P Capital IQ, CB Insights, Thomson ONE, and Zephyr. Deals were categorized as PE-backed or not PE-backed. Headquarter locations of the buying and selling companies and transaction value were obtained for each deal when available. Results: A total of 68 deals were obtained of which 5 (7.4%) were PE-backed. The buyer and seller were located in the same state in 50 (73.5%) of the deals. Transaction values were available for only four deals ranging from 2.52 million to 35 million. Conclusion: Our results suggest that consolidation of orthopaedic practices from 2010 to 2019 was driven by large healthcare entities rather than PE firms. Furthermore, intrastate acquisitions were markedly more common than interstate acquisitions, possibly because of greater legal feasibility and ease of clinical integration.